Calculation of doubly heavy baryons decay - Tyulemissov, Zh.Zh.; Issadykov, A.N.; Bekbaev, A.K.; Aznabaev, D.T.; Nurlan, K. (Recent Contributions to Physics, 2021)
We calculated a subclass of four nonleptonic two-body weak decays of the double charm baryon ground states . Nonleptonic decays can be divided into two group: factorizable and nonfactorizable decays. The first one can be easily calculated from first principles. Therefore, its good example understands all pros and cons of a model. We focused on a weak two-body nonleptonic decay consists only from the factorizing contribution precluding a contamination from W-exchange. We use the covariant confined quark model previously developed by us to calculate the various helicity amplitudes which describe the dynamics of the transition induced by the Cabibbo-favored effective currents. Achievement of CCQM is that only size parameter varying can describe all tree diagrams of nonleptonic decay. We then proceed to calculate the rates of the decay. The rates, branching ratios and helicity amplitude were calculated using dimensionless invariant form factors. Also, we calculated leptonic constant for scalar and vector mesons which has good agreement with experimental data. There isn’t any experimental data about the decay so we waiting for new experimental observation in the heavy baryon sector.